Implantable cardioverter-defibrillator therapy after resuscitation from cardiac arrest in vasospastic angina: A retrospective study - Kazuya Tateishi; Yusuke Kondo; Yuichi Saito; Hideki Kitahara; Kenichi Fukushima; Hidehisa Takahashi; Daichi Yamashita; Koichi Ohashi; Ko Suzuki; Osamu Hashimoto; Yoshiaki Sakai; Yoshio Kobayashi (PLoS ONE, 2022)
Patients with vasospastic angina (VSA) who are resuscitated from sudden cardiac arrest (SCA) are at a high risk of recurrent lethal arrhythmia and cardiovascular events. However, the benefit of the implantable cardioverter-defibrillator (ICD) therapy in this population has not been fully elucidated. The present study aimed to analyze the prognostic impact of ICD therapy on patients with VSA and SCA. A total of 280 patients who were resuscitated from SCA and received an ICD for secondary prophylaxis were included in the present multicenter registry. The patients were divided into two groups on the basis of the presence of VSA. The primary endpoint was a composite of all-cause death and appropriate ICD therapy (appropriate anti-tachycardia pacing and shock) for recurrent ventricular arrhythmias. Of 280 patients, 51 (18%) had VSA. Among those without VSA, ischemic cardiomyopathy was the main cause of SCA (38%), followed by non-ischemic cardiomyopathies (18%) and Brugada syndrome (7%). Twenty-three (8%) patients were dead and 72 (26%) received appropriate ICD therapy during a median follow-up period of 3.8 years. There was no significant difference in the incidence of the primary endpoint between patients with and without VSA (24% vs. 33%, p = 0.19). In a cohort of patients who received an ICD for secondary prophylaxis, long-term clinical outcomes were not different between those with VSA and those with other cardiac diseases after SCA, suggesting ICD therapy may be considered in patients with VSA and those with other etiologies who were resuscitated from SCA.